Ascorbic Acid Alleviates Toxicity Induced by Excess Copper in Brassica campestris Ssp. Chinensis Makino. Issue 6 (26th March 2017) - Zhou, J. J.; Ren, J.; Wang, X. H.; Liu, T. K.; Hou, X. L.; Li, Y.
ABSTRACT: In this study, the changes in mineral elements content, chlorophyll, malondialdehyde (MDA), ascorbic acid (AsA), and deoxyribonucleic acid (DNA) methylation level were studied in leaves of three cultivars of non-heading Chinese cabbage ( Brassica campestris ssp., chinensis Makino) under copper stress, and the role of exogenous AsA was also investigated. Under copper stress, the copper content in leaves increased significantly, while it is lowest in "Wutacai", which showed the highest copper tolerance in the three cultivars of non-heading Chinese cabbage. Mineral elements such as iron (Fe), manganese (Mn), magnesium (Mg), sodium (Na), and potassium (K) reduced remarkably, the content of chlorophyll decreased, while MDA and DNA methylation level increased significantly. Compared with that under copper treatment, exogenous AsA decreased the contents of copper and MDA, and DNA methylation level, while increased the content of chlorophyll and other mineral contents, which implied that AsA alleviates copper stress in non-heading Chinese cabbage.